Trends in HIV acquisition, risk factors and prevention policies among youth in Uganda, 1999-2011 - Santellia, John S.; Edelsteina, Zoe R.; Weia, Ying; Mathura, Sanyukta; Songa, Xiaoyu; Schuylera, Ashley; Nalugoda, Fred; Lutalo, Tom; Gray, Ron; Wawerd, Maria; Serwadda, David (AIDS, 2015)
The objective of this study is to understand how trends in HIV acquisition among youth can be influenced by change in HIV risk factors, social factors and prevention and treatment programmes. Design: Trends in HIV incidence (per 1000 person-years), by sex and age group, were estimated using data from youth (15–24 years: n = 22 164) in the Rakai Community Cohort Study. Trends in HIV incidence were compared with trends in previously identified HIV risk factors, social factors and programmes. Methods: Poisson and linear regression were used to test for statistical significance and decomposition was used to calculate attribution of risk factors to HIV incidence. Results: Substantial declines between 1999 and 2011 occurred in sexual experience, multiple partners and sexual concurrency among adolescents and young adults. HIV acquisition declined substantially (86%, P = 0.006) among adolescent women (15–19 years) but not among men or young adult women. Changes in HIV incidence and risk behaviours coincided with increases in school enrolment, decline in adolescent marriage, availability of antiretroviral therapy (ART) and increases in male medical circumcision (MMC). Much of the decline in HIV incidence among adolescent women (71%) was attributable to reduced sexual experience;the decline in sexual experience was primarily attributable to increasing levels of school enrollment. Conclusion: Dramatic decreases in HIV incidence occurred among adolescent women in Rakai. Changes in school enrollment and sexual experience were primarily responsible for declining HIV acquisition over time among adolescent women. Given limited improvement among young men and young adult women, the need for effective HIV prevention for young people remains critical.
Keywords: education; HIV incidence; HIV risk; sexual behaviour; youth